2014
DOI: 10.1371/journal.pone.0086293
|View full text |Cite
|
Sign up to set email alerts
|

LcMYB1 Is a Key Determinant of Differential Anthocyanin Accumulation among Genotypes, Tissues, Developmental Phases and ABA and Light Stimuli in Litchi chinensis

Abstract: The red coloration of litchi fruit depends on the accumulation of anthocyanins. The anthocyanins level in litchi fruit varies widely among cultivars, developmental stages and environmental stimuli. Previous studies on various plant species demonstrate that anthocyanin biosynthesis is controlled at the transcriptional level. Here, we describe a litchi R2R3-MYB transcription factor gene, LcMYB1, which demonstrates a similar sequence as other known anthocyanin regulators. The transcription levels of the LcMYB1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 63 publications
10
105
0
Order By: Relevance
“…Among these, co-expression of two classes of TFs, R2R3-MYB, and bHLH, is indispensable for the activation of anthocyanin biosynthetic genes (Bovy et al 2002;Butelli et al 2008). Also, work in Chinese berry and Litchi chinensis reported a requirement for an endogenous bHLHtype TF as a binding partner for anthocyanin-promoting MYBs (Huang et al 2013a;Lai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, co-expression of two classes of TFs, R2R3-MYB, and bHLH, is indispensable for the activation of anthocyanin biosynthetic genes (Bovy et al 2002;Butelli et al 2008). Also, work in Chinese berry and Litchi chinensis reported a requirement for an endogenous bHLHtype TF as a binding partner for anthocyanin-promoting MYBs (Huang et al 2013a;Lai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in grapevine ( Vitis vinifera ), VvMYBA1 and VvMYBA2 are responsible for anthocyanin biosynthesis in red-skinned cultivars [14]. GmMYB10 , MrMYB1 , PcMYB1 , and LcMYB1 are involved in the anthocyanin biosynthetic pathway in mangosteen ( Garcinia mangostana ), Chinese bayberry ( Myrica rubra ), pear ( Pyrus pyrifolia ), and litchi (Litchi chinensis ), respectively [15,16,17,18]. In maize ( Zea mays ) seeds, anthocyanin biosynthesis is regulated by C1 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Athocyanins biosynthesis is regulated by enzyme-coding structural genes, including chalcone synthase (CHS), chalcone isomerase (CHI), flavonoid-3′-hydroxylase (F3’H), flavonoid-3′,5′-hydroxylase (F3′5′H), flavanone 3-hydroxylase (F3H), dihydroflavonol 4-reductase (DFR), anthocyanidin synthase (ANS), UDP-glucose: flavonoid 3- O -glucosyltransferase (UFGT), and is also orchestrated at the transcriptional level by MBW transcription factor (TF) complexes consisting of MYB, bHLH (basic helix-loop-helix) and WD40 (Koes et al, 2005; Saito et al, 2013; Xu et al, 2015). Recent researches have demonstrated that the MBW complex regulates the genes that encode enzymes specifically at the late steps of the anthocyanin pathway, and the MYB TF s have been identified to be the major determinant regulatory genes in the biosynthetic steps of anthocyanin metabolism (Gonzalez et al, 2008; Lai et al, 2014; Shen et al, 2014). AtPAP1 ( AtMYB75 ), the known anthocyanin regulator originally defined in Arabidopsis, has been shown to effectively induce anthocyanin accumulation in various plant species (Zuluaga et al, 2008; Rowan et al, 2009; Li X. et al, 2010; Qiu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%